Impact of COVID–19-Related Stress and Lockdown on Mental Health Among People Living With HIV in Argentina. (1st December 2020) - Ballivian, Jamile; Alcaide, Maria L.; Cecchini, Diego; Jones, Deborah L.; Abbamonte, John M.; Cassetti, Isabel
Abstract : Background: The spread of severe acute respiratory syndrome coronavirus 2, causative agent of the coronavirus disease 2019 (COVID-19), has necessitated widespread lockdown to mitigate the pandemic. This study examines the influence of resilience on the impact of COVID-related stress and enforced lockdown on mental health, drug use, and treatment adherence among people living with HIV (PLWH) in Argentina. Setting: PLWH residing predominantly in Buenos Aires Metropolitan Area and urban regions of Argentina were identified from a private clinic electronic database. Methods: Participants completed an anonymous online survey to evaluate the impact of COVID-19 on economic disruption, resilience, mental health outcomes (depression, anxiety, stress, and loneliness), adherence to HIV treatment, and substance use. We performed ordinary least squares and logistic regressions to test whether resilient coping buffered the impact of economic disruption on mental health and drug use during quarantine. Results: A total of 1336 PLWH aged 18–82 were enrolled. The impact of economic disruption on mental health ΔF(1, 1321) = 8.86, P = 0.003 and loneliness ΔF(1, 1326) = 5.77, P = 0.016 was buffered by resilience. A 3-way interaction between resilient buffering, stress, and sex was significant ΔF(1, 1325) = 4.76, P = 0.029. Participants reported less than excellent adherence to medication (33%), disruption to mental health services (11%), and disruption to substance abuse treatment (1.3%) during lockdown. Discussion: The impact of COVID-stress and lockdown on emotional distress seemed mitigated by resilience coping strategies, and the buffering impact of resilience on perceived stress was greater among women. Results highlight PLWH's capacity to adhere to treatment in challenging circumstances and the importance of developing resilience skills for better coping with stress and adversity.